Economic feasibility of fish cage culture in Lake Victoria, Kenya. Issue 6 (9th October 2022) - Obiero, Kevin; Brian Mboya, Jimmy; Okoth Ouko, Kevin; Okech, Dave
Abstract: Fish cage culture has rapidly grown throughout Lake Victoria's shores, with Nile tilapia ( Oreochromis niloticus ) being the primarily cultured species. However, there is inadequate information on its economic viability. The study investigated the economic feasibility of fish cage farming system in Lake Victoria, Kenya, by evaluating the relationship between cost of inputs and revenue from fish sales and analysing the overall profitability of the fish cage culture in the lake. Systematic sampling was employed to select 200 cage farmers for the study. Structured questionnaire was used for data collection. Data was analysed using descriptive statistics, multiple regression analysis, gross margin analysis, net farm income and profitability ratios. The average quantity of fish produced in the production cycle was 11, 971.53 kg from which an average of 9020.77 kg was sold at an average selling price of Kenyan Shillings (KSH) 281.36 (USD 2.60) per kg. The multiple regression results revealed that the cost of feeds (coefficient of −0.603) and fish seed (coefficient of −0.387) had a significant influence on returns from fish cage culture business at p  < 0.01 and p  < 0.05, respectively. The costs of feeds and fish seed were significant components of the total production cost, accounting for 60.25% and 33.50%, respectively. Fish cage production was profitable, with an average gross margin of KSH 1146, 727.68 (USD 10, 545.59) and net farm income of KSH 1020, 518.78 (USD 9384.94) in a production cycle, with a benefit cost ratio of 1.43, an expense structure ratio of 0.06, a gross revenue ratio of 0.70 and a return on investment of 0.43. The study recommends formulation of friendly policies, legislations, operating guidelines and an enabling environment for feed and fish seed producers by policy makers to enhance fish feed and seed production and subsequently reduce prices of feed and seed. Through this, economic viability of fish cage culture will be enhanced. Abstract : The study analyzed the economic viability of cage fish culture in Lake Victoria, Kenya through analysis of input‐output relationship and profitability. The study revealed that cage fish farming in the lake is profitable and worthwhile.